PENGEMBANGAN BAHAN AJAR KOMIK BERBASIS CERITA RAKYAT DI SEKOLAH DASAR NEGERI KOTA BENGKULU - Ogy Agiustora; Abdul Muktadir; Nani Yuliantini (JURIDIKDAS, 2022)
This research aims to develop comicmaterials based onin Bengkulu City Elementary Schools. This type of research is the  Research and Development (R & D) with moedel ADDIE: Analyisis (Analysis),  Design (design), Development (development), Implementation (Implementation),  Evaluation (Evaluation). However, this research and development only reaches thestage Development . The validation was carried out by two material experts and one design expert. The teaching materials developed were rated by two grade IV teachers of 68 Elementary Schools in Bengkulu City. The data analysis technique used is descriptive statistical analysis of the results of expert validation assessments and teacher responses, and qualitative descriptive analysis of comments and suggestions from expert validation and teacher responses. From the results of the material expert validation, it was obtained a value of 89.3% with the very valid category, the design expert validation obtained a value of 96% with the very valid category. The recapitulation of values from the validation of material experts and design experts obtained an average of 92.95%. Teacher I's response obtained a value of 86.15% and teacher II's response obtained a value of 89.23% with a very valid category. The recapitulation of the value of the teacher's responses obtained an average of 87.69%, so that the product of Comic Learning Materials based on Folklore is very valid and very feasible to use.  Keywords: Development, Teaching Materials, Comics, Folklore